Analysis and prevention of weld crater cracking in circumferential laser microwelding of automotive pressure sensors. (October 2021) - Kenda, Miha; Klobčar, Damjan; Nagode, Aleš; Bračun, Drago
Highlights: Autogenous laser welding produces concave end-crater in 17–4 PH that is prone to solidification cracking. Solidification cracking at weld end-crater causes weld leakage. The use of novel zigzag laser power ramp-down profile produces significantly shorter, discontinuous, and leakage free cracks. Abstract: An analysis presents a weld leakage problems of automotive pressure sensor, caused by weld crater cracking. A two-beam laser welding (TBLW) was used to weld a circumferential weld, which undesirably increases the probability of weld leakage by creating two weld end craters on a single weld. Microstructural analysis showed that microsegregation of alloying elements combined with imposed strains causes solidification cracking at the weld end crater. A novel "zigzag" laser power ramp-down was used and the results showed a limited crack propagation by producing significantly shorter discontinuous cracks. In such weld crater endings the leakage is no longer an issue.